Identification of Plasmodium falciparum antigens by antigenic analysis of genomic and proteomic data - Doolan, Denise L. (National Academy of Sciences, 2003)
The recent explosion in genomic sequencing has made available a wealth of data that can now be analyzed to identify protein antigens, potential targets for vaccine development. Here we present, in the context of Plasmodium falciparum, a strategy that rapidly identifies target antigens from large and complex genomes. Sixteen antigenic proteins recognized by volunteers immunized with radiation-attenuated P. falciparum sporozoites, but not by mock immunized controls, were identified. Several of these were more antigenic than previously identified and well characterized P. falciparum-derived protein antigens. The data suggest that immune responses to Plasmodium are dispersed on a relatively large number of parasite antigens. These studies have implications for our understanding of immunodominance and breadth of responses to complex pathogens.